Influencing the Post 2020 Global Biodiversity Framework (an interim, evolving outcome) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
CCAFS (with the Genebank Platform) developed a written submission to the 23rd session of Convention on Biological Diversity's Subsidiary Body on Technical and Technological Advise, and convened a side-event at the same meeting, arguing that the Post-2020 Global Biodiversity Framework should promote the Plant Treaty (and more use of PGRFA). The Plant Treaty and increased PGRFA use were subsequently included in the first full draft of the Post-2020 Framework (which is still subject to further negotiations),